Transformational leadership and organizational citizenship behavior: new mediating roles for trustworthiness and trust in team leaders - Lee, Michelle Chin Chin *; Lin, Mei Hua *; Srinivasan, Priyadarshini Moharkonda; Carr, Stuart C. (Springer Verlag (Germany), 2023)
This study investigates the pivotal role of trust in bridging the effects of transformational leadership on organizational citizenship behavior (OCB). The study was conducted using a multilevel longitudinal approach with 276 employees in 71 teams from private medium-sized organizations in Kuala Lumpur, Malaysia. Transformational leadership was found to be positively related to: (1) three facets of trustworthiness (ability, benevolence, and integrity); (2) trust in the leader; and (3) OCB. All three facets of trustworthiness mediated the relationship between transformational leadership and trust in leaders. In addition, trust in the leader mediated only the relationship between the benevolence facet of trustworthiness and OCB. As OCB is inherently benevolent, these findings not only are consistent with the principle of compatibility, but they also contribute to theorizing about ‘how’ trust plays an important role in the influence of transformational leadership on employees.